Coexistence of pulmonary sclerosing hemangioma and primary adenocarcinoma in the same nodule of lung - Zhao Yong; Li Yang; Tian Xiao-Ying; Liu Wei; Li Bin; Li Zhi (BMC, 2011)
Abstract Pulmonary sclerosing hemangiomas (PSH) of the lung are uncommon tumors and may present cytological atypia with unusual manifestations. The development of PSH combined with other different tumors in lung is extremely rare. We report a case of coexistence of PSH and primary adenocarcinoma in a young female occurring in the same pulmonary nodular mass of right lower lobe. The solitary mass of lung was well-circumscribed on chest computed tomography (CT) and gross examination. Histologically, the mass contained two separated portions and displayed typically histological features of PSH and acinar adenocarcinoma, respectively. In PSH portion, the tumor was composed of sheets of round cells with scattered surface cuboidal cells forming small tubules. Both round and surface cells were diffusely positive for epithelial membrane antigen (EMA) and thyroid transcription factor-1 (TTF-1), but lack immunoreactivity for pancytokeratin in round cells. In adenocarcinoma portion, the tumor cells formed irregular-shaped glands with cytologically malignant cells infiltrating in fibroblastic stroma, and no TTF-1-positive round cells could be observed in this portion. Under the microscopy, there was no gradual transition of these two portions observed in mass. A diagnosis of PSH combined with primary adenocarcinoma of lung was made. There was no evidence of tumor recurrence during the period of postoperative 6-month follow-up. To our knowledge, this is the first case of coexistence of PSH and adenocarcinoma in the same nodule of lung. In addition, the biological behavior and histological differential diagnosis of this tumor were also discussed.